Replication timing of pseudo-NORs - Smirnov, Evgeny; Cmarko, Dušan; Kováčik, Lubomír; Hagen, Guy M; Popov, Alexey; Raska, Otakar; Prieto, José-Luis; Ryabchenko, Boris; Amim, Filipa; McStay, Brian; Raska, Ivan (Journal of structural biology, 2011)
In mammalian cells, transcriptionally active ribosomal genes are replicated in the early S phase, and the silent ribosomal genes in the late S phase, though mechanisms of this timing remain unknown. UBF (Upstream Binding Factor), a DNA binding protein and component of the pol I transcription machinery, is considered to be responsible for the loose chromatin structure of the active rDNA. Here we question whether such structure alone can ensure early replication of DNA. We investigate this problem on the model of pseudo-NORs, the tandem arrays of heterologous DNA sequence with high affinity for UBF, introduced into human chromosomes. Such arrays are not transcribed, yet efficiently bind UBF and mimic the chromatin structure of active rDNA. In our study, a human derived stable cell line containing one pseudo-NOR on the chromosome 10 was transiently transfected with UBF-GFP and PCNA-RFP, which allowed us to observe in vivo the growth of pseudo-NORs resulted from their replication. We found that replication of pseudo-NORs is not restricted to the early S phase, but continues in the late S phase at a significant level. These results were confirmed in the experiments with incorporation of thymidin analog EdU and BrdU ChIP assay. Similar results were obtained with another cell line containing pseudo-NOR on the chromosome 7. Our data indicate that the specific loose structure of chromatin, produced by the architect protein UBF, is not sufficient for the early replication.
Keywords: S Phase; proliferační antigen buněčného jádra; ribozomální DNA; DNA, Ribosomal; Humans; nádorové buněčné linie; lidé; imunohistochemie; Nucleolus Organizer Region; Pol1 Transcription Initiation Complex Proteins; Immunohistochemistry; Cell Line, Tumor; transkripční iniciační komplex Pol1 - proteiny; organizátor jadérka; Proliferating Cell Nuclear Antigen; S fáze